Effect of reciprocity on public opinion of international climate treaties: experimental evidence from the US and China. (14th September 2019) - Stroik, Paul; Chakraborty, D.; Ge, W.; Boulter, J.; Jamelske, E.
ABSTRACT: This study reports survey results of American and Chinese citizens administered to determine the effect of reciprocity and the absence of reciprocity on public support of international climate treaties. American and Chinese college students and adults were surveyed about their support for signing an international climate treaty including commitments to reduce their greenhouse gas emissions, conditional on the other country signing the same treaty or not. This study finds knowledge of other-country non-support on average decreases cooperative behaviour among all age groups in both the US and China. Knowledge of China's support for the treaty is found on average to increase support among American adults, while having no noticeable effect on average support among American college students. Chinese citizens are found to not respond positively to reciprocity. Although not statistically significant at conventional significance levels, knowledge of the US's support is found on average to decrease support among Chinese college students and adults. Key policy insights To increase support for international climate treaties, knowledge that another major emitter will sign the treaty does not unanimously increase domestic support. Knowing the other country will not sign the treaty decreases domestic support for signing an international climate treaty for both Americans and Chinese, relative to not being told about the other country's decision to sign the treaty. Knowing China will sign an international climate treaty on average increases American adult support for signing the same treaty, while American college student support is unaffected. Although not statistically significant at conventional significance levels, knowing the US will sign an international climate treaty on average decreases Chinese support for signing the same treaty. Policy-makers pursuing increased international support of climate treaties by first getting support from countries with substantial historical emissions might deter international support if little attention to fairness concerns is given.